Parents know better: Primary school choice and student achievement in London - Marco Ovidi (Queen Mary University of London, School of Economics and Finance, 2021)
Expanding parental choice in education may increase system-wide productivity if parents select schools that form a specifically good match with their children. I investigate the effect of attending a preferred school on student achievement in London primary schools. I exploit as good as random variation in admission to preferred schools arising from centralised assignment which awards school offer based on admission priority, residential distance, and parental preference. I compare students around year-specific catchment boundaries that cannot be exactly anticipated by parents. I find that attending the school of choice increases student achievement compared to an institution with lower parental preference but same value-added. Results suggest that parents select schools that are specifically effective in increasing their children's achievement, improving the efficiency of school seats allocation. I show that parents of low-ability males select schools with lower peer quality and these likely better suit their learning needs.
Keywords: H75; I21; I24; I28; 330; School choice; School effectiveness; Centralised assignment; Deferred acceptance